Supply Chain Management Evidence from Tourism Industry in Greece - KOT, Sebastian; KOZICKA, Katarzyna (Journal of Environmental Management and Tourism, 2018)
The article aims is presentation of Supply Chain Management issues introduced in tourism enterprises. The tourist product constitutes a mixture of services and resources offered and controlled by several businesses, organizations and authorities, implementation of SCM with the common responsibility allow for development of actions along with a cooperative atmosphere among all tourist partners. The paper consists of investigating the tourism development with SCM introduction and the study results on SCM introduction in chosen Greek enterprises located in Crete Island. Based on the obtained preliminary results, the performance trends of the tourist chain elements have been elaborated in order to increase their efficiency.